Screening for resistance to four fungal diseases and associated genomic regions in a snap bean diversity panel - Campa, Ana; Geffroy, Valérie; Bitocchi, Elena; Noly, Alicia; Papa, Roberto; Ferreira, Juan José (Frontiers in Plant Science, 2024)
Anthracnose, white mold, powdery mildew, and root rot caused by Colletotrichum lindemuthianum, Scletorinia sclerotiorum, Erysiphe spp., and Pythium ultimum, respectively, are among the most frequent diseases that cause significant production losses worldwide in common bean (Phaseolus vulgaris L.). Reactions against these four fungal diseases were investigated and genomic regions involved in resistance were identified using a genome-wide association study of 311 snap bean lines, a group of common beans whose immature pods can be consumed. The highest number of resistant lines was observed against the three C. lindemuthianum isolates evaluated: 156 lines were resistant to CL124 isolate, 146 lines resistant to CL18, and 109 lines were resistant to C531 isolate.being resistant to the CL124, CL18, and C531 isolates, respectively. Two well-known anthracnose resistance clusters were identified, the Co-2 on chromosome Pv11 for isolates CL124 and CL18, and the Co-3 on chromosome Pv04 for isolates CL124 and C531. In addition, other lesser-known regions of ANT anthracnose resistance were identified on chromosomes Pv02, Pv06, Pv08, and Pv10. For the white mold isolate tested, 24 resistant lines were identified and the resistance was localized to three different positions on chromosome Pv08. For the powdery mildew local isolate, only 12 resistant lines were identified, and along with the two previous resistance genes on chromosomes Pv04 and Pv11, a new region on chromosome Pv06 was also identified. For root rot caused by Pythium, 31 resistant lines were identified and two main regions were located on chromosomes Pv04 and Pv05. A total of 20 lines showed resistant or intermediate responses against four or five isolates. Relevant information for snap bean breeding programs was provided in this work. Snap bean lines with broad disease resistance were identified, which are suitable for sustainable farm production and for use as resistance donors. Potential genes and genomic regions to be considered for targeted improvement were provided, including new or less characterized regions that should be validated in future works. Powdery mildew disease was identified as a potential risk for snap bean production and should be considered a main goal in breeding programs.